Editorial: critical media literacy in teacher education - Pranaitytė, Lina; Haus, Michael (heiEDUCATION journal, 2023)
While for some of those engaged in teacher education the term ‘critical media literacy’ might be daunting, others might immediately sense fascination and curiosity. As for us, we believe that one should not be dismayed by such phrases too quickly just because they may not be as prominent in popular discourses or require a pause to grasp their full essence. Each and every single word in it bears a load of meaning, while all of them taken together hold timely, educationally valuable and purposeful content and practice. In fact, critical media literacy (CML) may be regarded as one of various crucial future literacies to be facilitated in teacher education and schools. In this heiEDUCATION special issue we aim to reveal the main points behind the framework of CML and simultaneously to emphasize its need in (teacher) education. - - In an effort to unpack the ideas of how CML figures in pre-service teacher education across the Atlantic, we jointly conceptualized and carried out a virtual lecture series entitled Critical Media Literacy: A Challenge for Teacher Education and Beyond. From June to November 2021 we took turns between Heidelberg and New York and delved into the CML inquiries from different disciplinary and pedagogical angles. The present heiEDUCATION issue encompasses a significant part of the presentations that were live-streamed to the interested public. All authors are teacher educators and bring their specific expertise and experience in approaching and teaching through the CML framework.